Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pelayanan Petugas Puskesmas di UPT BLUD Puskesmas Pemenang Kabupaten Lombok Utara - Asmadi, Andi; Menap, Menap; Khalik, Lalu Abdul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to identify the dominant factors that influence the performance of health services at the UPT BLUD Puskesmas Pemenang. This study used a cross-sectional design with 60 respondents. Data collection was carried out through questionnaires. Data analysis used Spearman correlation to test the relationship between variables such as competence, discipline, and service facilities, and their impact on service quality. The results showed that (1) the competence and discipline of health workers were the most significant factors influencing service performance; (2) competence showed a strong positive correlation with service performance (ρ = 0.828, p < 0.001), which means that skilled staff can provide more effective services; (3) discipline had a substantial positive impact (ρ = 0.760, p < 0.001), which means that the importance of compliance with protocols and schedules; (4) the availability of adequate facilities had a moderate effect on service performance (ρ = 0.342, p = 0.008). This confirms that improving the performance of health services in Community Health Centers requires a comprehensive approach, so that continuous professional development to improve staff competence, discipline enforcement, and strategic investment in service infrastructure is very important.